Verfälschung der Atemalkoholkonzentration: Messung durch ein „Hausmittel“ zur Zahnpflege? - Schaul, Martine; Schmitt, Georg; Skopp, Gisela; Haffner, Hans-Thomas (Rechtsmedizin, 2017)
A 43-year-old man claimed that a breath alcohol concentration (BrAC) of 0.32 mg/l detected by a Dräger Alcotest 7110 Evidential was due to the application of a homemade dental care remedy approximately three hours prior to the measurement. Repeated BrAC measurements were carried out with the accused using a sample of his homemade paste. Following application of the ethanol-containing paste, mouth alcohol was detected for a period of 2 h, but was identified reliably as mouth alcohol by Dräger Alcotest 7110 Evidential. This detection is guaranteed by an analytic procedure that has not yet been mentioned in any publication by Dräger. It is based on a continuous measurement of BrAC by an infrared sensor during breath sampling. Further studies are required to verify if the Dräger Alcotest 7110 Evidential device will also enable a sensitive detection of mouth alcohol in an inebriated state.